PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ZOOM DALAM PEMBELAJARAN TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SMA SWASTA YPK MEDAN TA.2021/2022 - Intan Purnama Sari; Cita Ayni Putri Silalahi (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of using zoom learning media on the learning outcomes of class X students at YPK Private Senior High School Medan. This type of research uses quantitative research by distributing questionnaires and tests with a sample of 40 students of class X SMA Private YPK Medan. In accordance with the hypothesis that the author formulated in this study, it was as follows: